Coviewing Educational Media: Does Coviewing Help Low-Income Preschoolers Learn Auditory and Audiovisual Vocabulary Associations? - Preeti G. Samudra; Rachel M. Flynn; Kevin M. Wong (SAGE Publishing, 2019)
Coviewing media is a practice commonly recommended to parents of young children. However, little is known about how coviewing might scaffold the vocabulary learning of low-income preschoolers. The present study focused on how coviewing educational media influences children's learning of two different vocabulary associations-auditory-only and audiovisual vocabulary associations. We additionally studied whether children with weaker baseline vocabularies might particularly benefit from coviewing. One hundred twenty-eight low-income preschoolers viewed five educational media clips either with an adult coviewer or alone. Audiovisual and auditory vocabulary associations were then assessed. Results show that coviewing did not support vocabulary learning overall but did specifically support the development of auditory-only vocabulary associations for children with weaker baseline vocabularies. This suggests that coviewing may not provide a ubiquitous benefit but rather predicts learning in the mode of coviewer input (auditory) specifically for the children who need additional supports the most.